Effect of Meniran Extract (Phyllanthus niruri) on Egg Hatcability of Carp (Cyprinus carpio L.) with Different Soaking Time - Fatian, Adella Spextania; Sarjito, Sarjito; Chilmawati, Diana (Jurnal Media Akuakultur Indonesia, 2023)
Goldfish (Cyprinus carpio) is a freshwater fish species that is highly favored in aquaculture due to the ease of its seed production, and the demand for goldfish seed sales is increasing. A constraint that affects the success rate of goldfish farming is the emergence of fungal infections during egg hatching stages. One of the efforts that can be made to prevent fungal infections during goldfish egg hatching is by immersing the eggs in meniran extract (Phyllanthus niruri) for a certain duration to achieve the best results. The purpose of this study was to determine the effect of the duration of meniran extract immersion on carp eggs, which provides the best hatching rate and larval survival and is free from fungal attacks. The test materials used were meniran extract solution and carp eggs. The method used was an experiment with a completely randomized design (CRD) with 5 treatments, each with 3 replications with different durations of meniran extract immersion. Treatments A (0 minutes), B (10 minutes), C (20 minutes), D (30 minutes), and E (40 minutes) The results of the study showed that the immersion of Phyllanthus niruri extract solution had a significant effect (P 0.05) on the hatchability and survival rate of Cyprinus carpio with regards to the prevalence of fungus but did not have a significant effect (P > 0.05) on the yolk sac absorption time. The optimal immersion time for Phyllanthus niruri extract on Cyprinus carpio eggs with regards to the prevalence of fungus, hatchability, and survival rate of the larvae was in treatment D (30 minutes), which resulted in a prevalence of fungus of 5.33 2.52%, a hatching rate (HR) of 94.54 2.52%, and a larval survival rate (SR) of 93.1 1.62%.